Chitosan induced cold tolerance in Kobresia pygmaea by regulating photosynthesis, antioxidant performance, and chloroplast ultrastructure - Li, Shuo; Sun, Haoyang; Zhang, Ruolin; Gao, Cai; Yang, Peizhi; He, Xueqing; Hu, Tianming (Frontiers in Plant Science, 2024)
Cold stress is the primary factor that limits the growth and development of Kobresia pygmaea in the Tibetan Plateau, China. Chitosan (CTS) has been recognized for its ability to enhance agricultural production and tolerance to stress. This study examined the effect of treating seedlings under cold stress with chitosan. The results demonstrated that cold stress inhibited the growth of seedlings and adversely affected the photosynthetic capacity (net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), maximum efficiency of photosystem II (Fv/Fm), quantum yield of photosystem II (φPSII), electron transport rate (ETR), and non-light-induced nonphotochemical fluorescence quenching Y(NPQ)), and destroyed PSII and the chloroplast structure. Under regular temperatures, low concentrations of CTS (0.005% and 0.01%) inhibited the soluble protein content, ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco, EC 4.1.1.39) activity, and photosynthetic capacity. However, the application of 0.015% CTS increased the levels of soluble sugar, fructose and protein, as well as those of the levels of ions, such as iron and magnesium, chlorophyll, photosynthetic capacity, and the activities of Rubisco, superoxide dismutase and phenylalanine amino-lyase (PAL). Under cold stress, treatment with CTS decreased the contents of starch and sucrose, improved the contents of fructose, soluble protein, and antioxidants, such as ascorbic acid and glutathione; enhanced the photosynthesis capacity; and the activities of Rubisco, chitinase and PAL. Exogenous CTS accelerated the development of the vascular bundle, mitigated the damage to chloroplast structure induced by cold and promoted the formation of well-organized thylakoids and grana lamellae. Additionally, CTS upregulated the expression of genes related to cold tolerance in K. pygmaea, such as KpBSK2/KpERF/KpDRE326. These findings indicate that CTS enhances the cold tolerance in K. pygmaea by improving development of the vascular bundle, increasing the accumulation of solutes and antioxidants, regulating the transformation of carbohydrates, repairing the chloroplast structure, and maintaining the photosynthetic capacity and Rubisco activity.